THE INFLUENCE OF BASRENG PRODUCT INNOVATION ON THE COMPETITIVENESS OF THE UD SANJAYA SOUTH LAMPUNG (NATAR) FOOD FACTORY - Jihan Indrianti Putri; M. Oktaviannur (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
One of the snack manufacturers in South Lampung, particularly in the Natar region, where the snack sector is highly competitive, is UD Sanjaya. The purpose of this study is to examine how the competitiveness of the UD Sanjaya food factory in South Lampung, Natar, is impacted by product innovation, product quality, and basreng design. The author bases the question, "Is there an effect of Competitiveness on Product Innovation in Basreng?" on this. This study aims to evaluate UD Sanjaya's competitiveness in the snack market and ascertain how basreng product innovation affects the company's competitiveness. Competitiveness (Y) is the dependent variable, whereas product innovation (X1), product quality (X2), and packaging design (X3) are the independent factors under investigation. This study's methodology is quantitative analysis, and consumer surveys were employed to gather data. The study's findings suggest that product innovation significantly and favorably affects competitiveness since it can boost customer loyalty and attention. Additionally, because consumers are choosing higher-quality products more and more, product quality has a big influence on the present. Due to its ability to affect how consumers view a product, attractive and useful packaging design is also crucial for boosting competitiveness. Overall, this study concludes that the three variables interact with each other and contribute to increasing the competitiveness of UD Sanjaya. Therefore, the company is advised to continue to innovate and improve the quality and design of product packaging to maintain and improve its market position.